THE ROLE OF DENTAL SURGEONS ON PATIENT CARE WITH REGARDS TO POTENTIALLY MALIGNANT DISORDERS AND ORAL CANCER - Goldemberg, Daniel Cohen (Revista Científica do CRO-RJ (Rio de Janeiro Dental Journal), 2020)
In order to understand how dentists should act when approaching patients that can present with cancer or precancer of the oral cavity, it is adamant that the professionals familiarize themselves with the current trends of oral cancer and potentially malignant disorders. A study conducted only three years ago pinpointed that squamous cell carcinoma of the head and neck has a five-year survival rate of only 40 to 60% in fifty years, despite advances in surgical techniques, radiotherapy, chemotherapy and combined therapies.1 In order to avoid these terrible statistics, a great effort must be made by medical professionals, especially those that constantly examine the oral cavity, also known as: dentists.